2017
DOI: 10.1200/jgo.2017.009472
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Patient Navigator on Time to Diagnosis Among Pediatric Oncology Patients in Tanzania

Abstract: 12 Background: Oncology patient navigation programs have been successfully implemented at hospitals throughout the United States and have enhanced the quality of care through financial guidance, treatment coordination, and psychosocial support. In low-resource settings, barriers to receiving cancer care are increased and a patient navigator in this setting has the potential to significantly impact outcomes; however, there is limited research on the efficacy of such programs in these settings. At Bugando Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies support patient navigators being part of cancer care in resource limited settings. A retrospective study in one of the medical centers in Tanzania showed significant impact of patient navigators in patient outcomes of pediatric cancers through reduced time to evaluation and diagnosis from 49.7 days to 16.6 days (p = 0.02) as well as in decreased rate of abandonment 50% to 38% (p < 0.001) (Alvi et al, 2017). A local study involving breast cancer patients noted a decreased attrition rate 62% to 18% (p<0.0001) and improved quality of life of breast cancer patients after navigation program was employed (Patdu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support patient navigators being part of cancer care in resource limited settings. A retrospective study in one of the medical centers in Tanzania showed significant impact of patient navigators in patient outcomes of pediatric cancers through reduced time to evaluation and diagnosis from 49.7 days to 16.6 days (p = 0.02) as well as in decreased rate of abandonment 50% to 38% (p < 0.001) (Alvi et al, 2017). A local study involving breast cancer patients noted a decreased attrition rate 62% to 18% (p<0.0001) and improved quality of life of breast cancer patients after navigation program was employed (Patdu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%